Democracy under Patronage: A Marxist Analysis of Bureaucracy in the 2024 North Toraja Election - Sapta Samudera, Regina; T. Tikson, Deddy; Sangkala, Sangkala; Rusdi, Muhammad (Iapa Proceedings Conference, 2025)
The 2024 election in North Toraja Regency reflects local democracy still dominated by patronage practices, bureaucratic involvement, and money politics. This study employs a qualitative case study approach to analyze how bureaucracy functions not as a neutral instrument but as a political tool for elites, and how money politics is legitimized by society as part of economic rationality and cultural norms. Using Marxism, Gramsci’s theory of hegemony, and voter behavior theories (rational choice and patron–client), this research finds that local democracy in North Toraja represents elite power reproduction rather than substantive popular participation. In-depth interviews and focus group discussions reveal that kinship ties, campaign promises, and money politics are key determinants of voter behavior. The study concludes that elections in North Toraja remain an arena of capital and patronage contestation, with bureaucracy and money politics serving as instruments of elite hegemony. It recommends bureaucratic reform, voter political education, and law enforcement against money politics to improve the quality of local democracy.